Stories from My Childhood - Volume 3 - Ivanov-Vano, Ivan Petrovic; Degtjarëv, V.; Aksencuk, Ivan Semënovic; Parker, Sarah Jessica; Turner, Kathleen; Sheen, Martin (image Entertainment, 1999)
The story of Russia's Soyuzmultfilm Studios is one of the most fascinating chapters in 20th century animation. Begun in 1936 as a Soviet response to Disney's success, the organization eventually found its own house style, drawing some of the most talented writers, musicians, and filmmakers in the country, who in turn found relative freedom from government censorship. Another big plus for Soyuzmultfilm artists was its unhurried working conditions: animators had the luxury of time to create lush, painterly worlds from adapted folk tales. This third volume of vintage works from Soyuzmultfilm, originally broadcast on PBS with contemporary voicing by English-speaking actors and co-executive produced by Mikhail Baryshnikov, includes the lovely "The Snow Girl", in which an elderly couple wishing for a child creates one from snow. (The voice cast includes Amanda Plummer and Lolita Davidovich.) A Russian version of "Cinderella" (narrated by Sarah Jessica Parker) is also quite lovely, while "House on Chicken Legs" is a rousing cartoon version of Mussorgsky's Pictures from an Exhibition. Animation buffs will really marvel at the richness and variation from piece to piece in Soyuzmultfilm releases. Kids, however, may find a deeper experience than they do watching most contemporary U.S. animation. The DVD has alternate French and Spanish soundtracks with different vocal casts. (Tom Keogh) [www.amazon.com]